White matter tracts involved in subcortical unilateral spatial neglect in subacute stroke - Cha, Seungwoo; Jeong, ByeongChang; Choi, Myungwon; Kwon, Sohyun; Lee, Stephanie Hyeyoung; Paik, Nam-Jong; Kim, Won-Seok; Han, Cheol E. (Frontiers in Neurology, 2022)
Background Unilateral spatial neglect (USN) is common and associated with poor motor and cognitive outcomes as well as impaired quality of life following stroke. Traditionally, the neural substrates underlying USN have been thought to be cortical areas, such as the posterior parietal cortex. However, patients with stroke involving only subcortical structures may also present with USN. While only a few studies have reported on USN in subcortical stroke, the involvement of white matter tracts related to brain networks of visuospatial attention is one possible explanation for subcortical neglect. Therefore, this study aimed to investigate which specific white matter tracts are neural substrates for USN in patients with subcortical stroke. Methods Twenty-two patients with subcortical stroke without cortical involvement who were admitted to the Department of Rehabilitation Medicine at Seoul National University Bundang Hospital were retrospectively enrolled. Nine subjects were subclassified into a “USN(+)” group, as they had at least two positive results on three tests (the Schenkenberg line bisection test, Albert’s test, and house drawing test) and a score of 1 or higher on the Catherine Bergego scale. The remaining 13 subjects without abnormalities on those tests were subclassified into the “USN(−)” group. Stroke lesions on MRI were manually drawn using MRIcron software. Lesion overlapping and atlas-based analyses of MRI images were conducted. The correlation was analyzed between the overlapped lesion volumes with white matter tracts and the severity of USN. Results Lesions were more widespread in the USN(+) group than in the USN(−) group, although their locations were similar. The atlas-based analyses identified that the right cingulum in the cingulate cortex, the temporal projection of the superior longitudinal fasciculus, and the forceps minor significantly overlapped with the lesions in the USN(+) group than in the USN(-) group. The score of the Catherine Bergego scale correlated with the volume of the involved white matter tracts. Conclusions In this study, white matter tracts associated with USN were identified in patients with subcortical stroke without any cortical involvement. Our study results, along with previous findings on subcortical USN, support that USN may result from damage to white matter pathways.